Analysis, modeling, and design considerations for the excitation systems of synchronous generators - Nuzzo, Stefano; Galea, Michael; Gerada, C.; Brown, Neil (Institute of Electrical and Electronics Engineers, 2018)
The traditional generating set is usually comprised of a classical, wound-field, salient-pole or cylindrical rotor synchronous generator, excited by a separate smaller machine, via a rotating, uncontrolled diode rectifier. The effects of the commutation processes of the diode bridge are often overlooked and neglected. However due to the uncontrolled nature of this process, the rectified voltage available at the main generator’s rotor terminals can be significantly lower than the expected value. This is especially true for low-to-medium power rated systems.